THE VALUE OF SERVICE; EXPLORING THE MODEL OF SERVICE QUALITY IN INDONESIAN AND TUNISIA ISLAMIC UNIVERSITY - Wildatul Islamiyah; Nurul Najma Kamila Hasyim (PEDAGOGIK : JURNAL PENDIDIKAN, 2024)
This research aims to understand the model of service quality based on Islamic values in Indonesia and Tunisia. The study is motivated by a lack of awareness regarding the importance of Islamic values in service, conflicts in values and cultures, insufficient resources and support, resistance from internal parties, consumer ignorance, differences in the interpretation of Islamic values, and the influence of political and economic contexts. The research employs a qualitative approach with a multisite design. To gather data in both countries, the researcher uses participant observation, in-depth interviews, and documentation. The collected data is analyzed using Miles, Huberman, and Saldana's data analysis techniques. The analysis shows that interpersonal interaction, empathy, and service reliability are essential in shaping students’ perceptions of service quality. The study identifies each university's challenges and strengths in providing quality service and highlights cultural differences that influence service experiences. The findings provide insight into how university administrators can improve service quality, emphasising the importance of listening to students’ voices and adapting service practices to needs.